CONCEPT OF TRANSFORMATION OF POLITICAL CULTURE AND ITS SCIENTIFIC BASIS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes political and cultural factors and their role in social development, as well as the transformation of the political culture of citizens in the new Uzbekistan on a scientific and creative basis. Special attention is paid to the concept of transformation and transformation of political culture. This article is important from a scientific, creative and analytical point of view. In particular, "political culture" is not a separate phenomenon of political mentality and national character. The American researcher R. Dalton emphasizes that political scientists have not paid attention to many other important aspects of his national mentality, socio-cultural and intellectual level. This approach is a clear example of a new approach to the concept of political culture. The article also draws scientific conclusions that transformational processes are formed in a specific situation and represent a kind of synthesis of the processes of functioning and development, allowing us to consider it as a dynamic system. The article is relevant today.